Effects of a moderate-intensity aerobic exercise programme on the cognitive function and quality of life of community-dwelling elderly people with mild cognitive impairment: A randomised controlled trial. (May 2019) - Song, Dan; Yu, Doris S.F.
Abstract: Background: Individuals with mild cognitive impairment have a heightened risk of developing dementia. Physical exercise, especially moderate-intensity aerobic exercise, is a promising lifestyle intervention to improve the cognitive function of this patient group. However, the mechanisms underlying the exercise–cognition relationship are not fully understood. Whether the cognitive benefits of physical exercise can improve the overall well-being of this group remains unknown. This study aims to address these research gaps in the under-researched Chinese population. Objectives: This study aimed to evaluate the effects of a moderate-intensity aerobic exercise programme on the cognitive function and health-related quality of life of Chinese elderly with mild cognitive impairment and to explore the mediating roles of depressive mood and sleep quality in the exercise–cognition relationship. Design: A single-blinded randomised controlled trial. Settings and participants: This study was conducted in two urban community healthcare centres in Hangzhou City, China. Elderly people aged over 60 years screened with mild cognitive impairment were included. Methods: A total of 120 eligible participants were randomly assigned to receive either the group-based moderate-intensity aerobic exercise programme or the health education programme (as attention–placebo control). Montreal Cognitive Assessment, Quality of Life-Alzheimer's Disease, Geriatric Depression Scale and Pittsburgh Sleep Quality Index were administered at baseline before randomisation and immediately after the completion of the interventions. Analysis followed the intention-to-treat principle. Generalised estimating equation was used to compare the changes in the cognitive function and health-related quality of life over the pre-test and post-test periods between the groups. The mediating roles of depressive mood and sleep quality in the exercise–cognition relationship were examined with the PROCESS macro. Results: Participants in the intervention group had a significantly greater improvement in terms of cognitive function (β = 1.895; 95% confidential interval [CI] = 1.421, 2.368; p < 0.001) and health-related quality of life (β= 0.605; 95% CI= 0.295, 0.914; p < 0.001) compared with the control group over the pre-test and post-test periods. The exercise–cognition relationship was significantly mediated by reduced depressive symptoms (indirect effect: β= −0.705; 95% CI: −1.028, −0.382) and improved sleep quality (indirect effect: β=−0.205; 95% CI: −0.122, 0.831). Conclusions: This study revealed the benefits and outlined the underlying mediating mechanism of an aerobic exercise programme to the cognitive function and health-related quality of life of Chinese elderly people with mild cognitive impairment. The findings provided insights into the development of public health initiatives to promote brain health amongst the elderly with mild cognitive impairment.